Physico-chemical properties of different formulations of pequi pulp with milk - Moraes, Maria Suiane; Esmero, Janaina Almeida Dantas; de Figueirêdo, Rossana Maria Feitosa; Queiroz, Alexandre José de Melo (Comunicata Scientiae, 2020)
The objective of this work was to perform the physical-chemical characterization of different formulations of the pequi pulp with the addition of different concentrations of whole milk, in order to identify promising products for commercial use. Three formulations of pequi pulp with whole milk were prepared: PL1- 90% pequi pulp and 10% milk, PL2 - 70% pequi pulp and 30% milk, PL3 - 50% pequi pulp and 50% milk. The formulations were evaluated for physical and physical-chemical parameters of color, water activity, water content, ash, total soluble solids (SST), pH, total titratable acidity (ATT), SST/ATT ratio, ascorbic acid, proteins, lipids, total, reducing and non-reducing sugars. The data obtained were subjected to analysis of variance (ANOVA) and comparison between means by the Tukey test at 5% probability. Among the three tested formulations, the best results were obtained for PL3, where it presented lower total titratable acidity, water activity, red intensity, yellow intensity and chromaticity, however, higher content of total soluble solids, ratio SST/ATT, ash, lipids, sugars (total, dimmer and non-dimmer), luminosity and tint angle. The inclusion of milk in the pequi pulp changed the physical and physical-chemical characteristics of the pulp, and it can be an alternative to add nutritional value to the fruit and consequently a promising product for the market.